Phototherapeutic effect of transformable peptides containing pheophorbide a on colorectal cancer. (31st December 2022) - Zhang, Zhiqin; Wang, Kaixin; Liu, Manting; Hu, Panxiang; Xu, Yuchen; Yin, Dongge; Yang, Yuchang; Dong, Xiaoxv; Qu, Changhai; Zhang, Lu; Ni, Jian; Yin, Xingbin
Abstract: Photodynamic therapy (PDT) and photothermal therapy (PTT) have attracted research interest for their noninvasive nature and selective treatment of tumor tissues. They are effective through the generation of reactive oxygen species (ROS) or heat. Nevertheless, several problems, including low bioavailability and long-lasting cutaneous photosensitivity, have limited their clinical application. In this study, we reported an in situ self-assembly strategy that could improve various biological properties of the photosensitizer in vivo . A photosensitizer connected to a receptor-mediated smart peptide can self-assemble into nanoparticles (NPs) under the force of hydrophobic interaction and then transform into a nanofibrillar network after attaching to the tumor cell surface with the help of the β-sheet-forming peptide KLVFF. The supramolecular structural changes deeply affected the PDT and PTT properties of the photosensitizer on tumors. After being aggregated into the nanostructure, the water solubility and targeting ability of the photosensitizer was ameliorated. Moreover, the improvement of the photothermal conversion efficiency, ROS generation, and tumor retention followed the formation of nanofibrils (NFs). This self-assembly strategy showed the ability of supramolecular nanofibrils to improve the bioavailability of photosensitizers, which provides a new potential treatment avenue for various cancer therapies.